Exploring the potential impact of adding upper limit single trigger MET thresholds to a paediatric early warning scoring tool at a tertiary children's hospital: a retrospective review - Shawn Steckle; Casey Fowler; Victoria Campbell (Frontiers in Pediatrics, 2024)
ObjectiveThis study aims to determine the impact of incorporating upper threshold vital sign triggers into the digital Children's Early Warning Tool (CEWT) on the number of medical emergency team (MET) alerts.MethodsDe-identified vital set data from the Cerner Millennium Integrated Electronic Medical Records were obtained for all paediatric patients aged ≤16 years at a tertiary children's hospital in Brisbane over a 12-month period in 2022. Patients in the paediatric intensive care unit, post-anaesthetic care unit, or the emergency department were excluded as they would not trigger MET alerts in these locations. Microsoft Excel scripts were used to tabulate and graph the data to compare the number of MET alerts in the current system vs. the system with proposed upper thresholds for heart rate, respiratory rate, systolic blood pressure, and severe respiratory distress.ResultsA total of 389,352 vital sets were used for analysis after exclusions. Total cumulative MET alerts increased by 229% from 1,707 to 5,623. The number of increased alerts was inversely proportional to the age group. Respiratory rate and systolic blood pressure were the vital signs most associated with increased alerts. The largest number of new alerts came from patients with lower CEWT scores, while the largest proportional increase in alerts came from those with higher CEWT scores.ConclusionsIncorporating upper threshold vital sign triggers into the digital CEWT leads to a substantial increase in MET alerts. The consequent workload is not justified, given the lack of evidence suggesting a failure of the current CEWT system in recognising deteriorating patients.